Enraizamento de miniestacas e nutrição mineral em minicepas de Eucalyptus urophylla S. T Blake - Lopes, Alessandra da Silva (2016)
The species of Eucalyptus urophylla is of great economic value and one of the most commercially used. In this context the vegetative propagation with minicutting technique stands out for being a lower cost of operation and is the most widely used method for cloning by virtually all forest companies. Another relevant factor is nutrition and rooting interaction. The optimal management of a minigarden in terms of mineral nutrition can provide propagules with a greater predisposition to anchor the latter being an essential step for the success of vegetative propagation. However, there is little information on the factors affecting mineral nutrition and relationship rooted in genetic material of seminal origin. Given the above the present study aimed to generate information about the adventitious rooting in minicuttings and evaluate mineral nutrition in ministumps of Eucalyptus urophylla through minicutting techniques. The study was divided into two chapters. The first study (Chapter 1) was based on the evaluation of the seminal minigarden in relation to different nutrient solution concentrations and shoot collections to issue pre-disposed to rooting. The second study (Chapter 2) was to evaluate the minicuttings as the morphological and rooting for the different concentrations of nutrient solution, collection and application of indol-3-butyric acid (IBA) and histological analysis of adventitious rooting in relation to solutions nutritious, IBA application and evaluation time. Overall the ministumps obtained 100% survival. The production of minicuttings and leaf contents of macro and micronutrients varied significantly in relation to the nutrient solution and shoot collections. Minicuttings significant variation in the amount of root length of the longest root, rooting and total height of minicuttings and the solution 75% and 100%, the 4th and 7th collected and the presence of IBA was favoring the growth and development the root system and the adventitious rooting. According to the histological analysis it was possible to check the insertion site of the adventitious root to stem from direct connection to the vascular cambium.